The Copper Plates of Helagupta: A New Edition and Study - Salomon, Richard (Indo-Iranian journal, 2020)
The article presents a new edition, translation, and interpretation of the inscription, which was previously published by H. Falk in 2014, of the otherwise unknown Buddhist patron Helagupta (helaüta). The inscription, datable to the latter half of the first century CE, is recorded on five copper plates and is the second longest one known in Kharoṣṭhī script/Gāndhārī language. This edition proposes several new readings and interpretations as well as discussing its cultural implications for issues such as the performance of ancestral rituals by Buddhists, and Buddhological ramifications such as the concept of “brahma merit” (Gāndhārī bramo puṇyo) and the contemporary understanding of variant forms of titles of the Buddha.